Ellagic acid alleviates motor, cognitive and hippocampal electrical activity deficits in the male rats with 2-vessel occlusion cerebral ischemia/reperfusion - Khadijeh Hassonizadeh Falahieh; Alireza Sarkaki; Mohammadamin Edalatmanesh; Mohammad Kazem Gharib Naseri; Yaghoob Farbood (Mashhad University of Medical Sciences, 2023)
Objective: Cerebral ischemia/reperfusion (I/R) has been known as a major cause of inability and mortality worldwide. Ellagic acid (EA) has many pharmacological effects including antioxidant, antithrombotic and neurorestoration activities. The aim of this study was evaluation of the effects of EA on motor and cognitive behaviors, hippocampal local field potential (LFP), brain oxidative stress in male rats with cerebral 2-vessel occlusion ischemia/reperfusion (2VO I/R).Materials and Methods: Forty-eight male Wistar rats (250-300 g) were assigned into six groups. 1) The Sham: rats were treated with DMSO10%/normal saline as solvent of EA 3 times daily for 1 week; 2) I/R+Veh; I/R rats received vehicle; 3-5) EA-treated groups: I/R rats received 50, 75, or 100 mg/kg EA; and 6) Cont+EA100: intact rats received EA. The cerebral 2VO I/R was made by the bilateral common carotid arteries closing for 20 min followed by reperfusion. The behavioral tests and hippocampal LFP recording were performed after treatment with EA. The oxidative stress parameters were assayed by special ELISA kits.Results: Cerebral 2VO I/R significantly decreased motor coordination, memory and hippocampal LFP and significantly increased oxidative stress. Treatment with EA improved all I/R complications. Conclusion: The current findings showed that treatment of I/R rats with EA could reverse cognitive and motor functions, and improve the LFP and oxidative stress markers. So, effects of EA on cognitive and motor function may at least in part, be due to its antioxidative actions.